Comparison of Efficacy of Moxifloxacin and Cefotaxime in the Treatment of Spontaneous Bacterial Peritonitis in Cirrhotic Patients - SAMAD, ABDUL; KHAN, MEHRAB; SIDDIQUI, SOHAIL AHMED; MEMON, RAMEEZ IQBAL; QALBANI, QURB ALI; ABRAR, MEHWISH (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Spontaneous bacterial peritonitis (SBP) is a life-threatening complication in cirrhotic patients, with high mortality rates if untreated. The study aimed to compare the efficacy of Moxifloxacin and Cefotaxime in the treatment of SBP in cirrhotic patients. Methodology: This was a randomized, double-blind, controlled clinical trial was conducted at Liaquat University Hospital Hyderabad from 1st October 2024 to 30th June 2025. A total of 130 cirrhotic patients diagnosed with SBP, who were randomly assigned to receive Moxifloxacin (400 mg daily) or Cefotaxime (2g every 8 hours) for 7 days were enrolled. The primary outcome was the resolution of infection, and secondary outcomes included clinical improvement, mortality rates, and adverse effects. Results: The infection resolution rate was 90% in the Moxifloxacin group and 85% in the Cefotaxime group. No significant differences in clinical improvement or mortality rates were observed. Adverse effects were minimal in both groups. Conclusion: Moxifloxacin appears to be equally effective as Cefotaxime in treating SBP in cirrhotic patients, with no significant differences in clinical outcomes. Further studies are needed to explore long-term outcomes and resistance patterns. Keywords: Spontaneous bacterial peritonitis, cirrhosis, Moxifloxacin, Cefotaxime, antibiotic treatment, clinical outcomes.